Media discourse and the Yugoslav conflicts : representations of self and other - Kolstø, Pål (Ashgate, 2009)
In spite of the growing literature on discourse analysis, the relationship of discourse to violent/non-violent outcomes of conflict is an under-researched area. This book combines theories on ethnic conflict, identity construction and discourse analysis with a comprehensive and inclusive survey of the countries of the former Yugoslavia. It will be of interest to those concerned with ethnopolitical conflict and scholars across a range of social sciences.